SOCIAL CONNECTEDNESS AND MENTAL HEALTH: THE CONTEXT OF CHINA AND CHINESE IMMIGRANT COMMUNITIES IN THE U.S. - Chen, F (Innov Aging, 2018)
The association between social connection and mental health is well established, but the extent and mechanisms of how social ties shape mental health outcomes are still not clearly understood. This symposium showcases the mental health significance of the multidimensionality of social connectedness in different settings. 1)Cong et al. address one type of family ties – intergenerational relationships in rural China, where the norm of filial piety and family support are fundamental to old age support. They map out the pathway of how children’s education and exchanges with older parents could affect the latter’s mental health. 2)Also focusing on filial piety, Xu et al. find that the discrepancy between filial receipts and expectations (in six domains) is strongly associated with anxiety and stress among older Chinese immigrants in the U.S. 3)Guo et al. further demonstrate the centrality of family/social relations for older Chinese immigrants in the U.S. They find that later-life migration (compared with earlier-life) is associated with higher levels of depression, possibly through weakened family and social relations. 4)Chen et al. examine social interaction within and beyond the household as key dimensions of social connectivity. Using innovative time diary data in rural China, they dissect “personal”, “family” and “social” time use and explore their relative roles in shaping old adults’ mental health. 5)Liu et al. focus on friends as an important part of the non-kin social network. They find mixed influences of losing friends on loneliness and the quality of life of older Chinese immigrants in the U.S.